Desenvolvimento de uma metodologia para a obtenção de informações sobre o saldo de radiação a partir da temperatura do ar em ecossistemas naturais - Prado, Marcos Fernando do (2017)
By using data of climatological variables, this study aims to extract net radiation (Rn) information from air temperature data (T), combining the Takens Theorem (1981) with the technique of rotation of the time-lagged space. The results of this study indicate that the rotation technique shows great potential in extracting information from a micrometeorological variable from other data measures, for the dry season. For the wet season, the procedure did not present good results. Therefore, Takens Theorem is valid concerning the reconstruction of the relationship between these variables.